Behavioural Stress Propagation in Benthic Invertebrates Caused by Acute pH Drop-Induced Metabolites - Lauric Feugere (Frontiers Media S.A., 2021)
Studies on pH stress in marine animals typically focus on direct or species-specific aspects. We here test the hypothesis that a drop to pH = 7.6 indirectly affects the intra- and interspecific interactions of benthic invertebrates by means of chemical communication. We recorded fitness-relevant behaviours of small hermit crabs Diogenes pugilator, green shore crabs Carcinus maenas, and harbour ragworms Hediste diversicolor in response to short-term pH drop, and to putative stress metabolites released by conspecifics or gilt-head sea bream Sparus aurata during 30 min of acute pH drop. Not only did acute pH drop itself impair time to find a food cue in small hermit crabs and burrowing in harbour ragworms, but similar effects were observed under exposure to pH drop-induced stress metabolites. Stress metabolites from S. aurata, but not its regular control metabolites, also induced avoidance responses in all recipient species. Here, we confirm that a short-term abrupt pH drop, an abiotic stressor, has the capacity to trigger the release of metabolites which induce behavioural responses in conspecific and heterospecific individuals, which can be interpreted as a behavioural cost. Our findings that stress responses can be indirectly propagated through means of chemical communication warrant further research to confirm the effect size of the behavioural impairments caused by stress metabolites and to characterise their chemical nature.